Politik Hukum Pengelolaan Sampah Dan Penutupan Tempat Pemrosesan Akhir (TPA) Piyungan: Daerah Istimewa Yogyakarta - Imam Hakiki; Resti Kurnia (Universitas Muhammadiyah Mataram, 2025)
This research provides an analysis of how the closure of the Piyungan landfill in the Special Region of Yogyakarta on March 5, 2024 marks a crisis in waste management due to the capacity that has exceeded its limits since 2012. Waste management policies that are still oriented towards an end-of-pipe approach have proven unsustainable and require transformation based on the political principles of environmental law. Regulations such as Law No. 18 of 2008 concerning Waste Management and Regional Regulation No. 3 of 2013 have provided a legal basis, but implementation still faces various challenges, including inter-regional coordination, lack of processing infrastructure, and community resistance to the construction of new landfills. This research uses a descriptive qualitative method with a political law approach to analyze the effectiveness of environmental policies in waste management in Yogyakarta. The results show that existing policies have not been able to overcome structural problems in waste management, especially related to the weak synergy between local governments, communities, and the private sector. This study recommends a paradigm shift from a conventional disposal system to a circular approach based on reduce, reuse, recycle (3R) supported by stricter regulations, strengthening economic incentives, and increasing public legal awareness of ecological responsibility